Analysis of Spindle Rotation Speed on Turning Results in CQ 6236 Lathe Machine - Fiqri, M. Shyadul; Arif Adlie, Taufan; Bahri Widodo, Syamsul (Fakultas Teknik Universitas Samudra, 2025)
The selection of turning speed is very important because the turning process affects the quality of the work, especially in the metal industry and small or medium-sized industries. To meet production needs, the rotational speed of the lathe can be adjusted to various spindle speed levels. Variations in speed will cause the workpiece to differ in terms of flatness and smoothness. The turning process begins with a linear motion along the axis of the AISI 1040 steel workpiece, with a slow feed of 2 mm. Smooth and even results were obtained at speeds of 80 rpm, 105 rpm, 160 rpm, 250 rpm, 380 rpm, 480 rpm, 750 rpm, and 1200 rpm. The turning test was conducted once with a diameter of 25 mm. The surface roughness from the turning process is influenced by various factors, including the spindle speed and the cutting angle used. Each workpiece processed on the machine tool certainly produces a different surface roughness. This research aims to determine the effect of the cutting angle and spindle speed on the surface roughness of AISI 1040 carbon steel. The Experimental Method is more suitable for this research to determine the effect of surface roughness and spindle rotation on AISI 1040 steel specimens. The material used has a diameter of 25 mm and a length of 80 mm, with a cutting depth of 2 mm. Meanwhile, the spindle speeds used were 1200 rpm, 750 rpm, 480 rpm, 380 rpm, 250 rpm, 160 rpm, 105 rpm, and 80 rpm. Surface roughness was measured using a surface roughness tester. The research results showed that the lowest surface roughness value in the specimen testing with a spindle speed of 1200 rpm was 0.679 µm, while the highest surface roughness was obtained at a spindle speed of 80 rpm, which was 5.260 µm. The conclusion of this research is that spindle speed affects the surface roughness value, where a smaller cutting angle results in a rougher surface, and a higher spindle speed results in a smoother surface.